EPIGLOTITIS AGUDA POR PREVOTELLA BUCCAE COMPLICADA CON MEDIASTINITIS - Rivero, Vicente Pino; Cuadri, Ángel Vega; García, Mónica Marcos; Garcia, Carlos Montero; Yáñez, Tamara Keituqwo; Albarrán, Afonso Ambel; Huelva, Antonio Blasco (Revista Portuguesa de Otorrinolaringologia-Cirurgia de Cabeça e Pescoço, 2005)
.